Fair Equality of Opportunity in Healthcare - Nunes, Rui (Conatus - Journal of Philosophy, 2018)
The allocation of resources for health, as well as the distribution of other social goods, being a political problem, can also be observed as belonging to the universe of distributive justice, considering that all citizens must have the necessary means for an acceptable physical, psychological and social performance. Individual autonomy, paradigm of a full citizenship in a modern society, cannot otherwise be achieved. Human dignity seems to imply that no citizen can be excluded from the basic health system due to the lack of financial resources. Indeed, equal access of all citizens to basic social goods and therefore to key places in society – principle of fair equality of opportunities – is one of the core aspects of Rawls's difference principle. It is, in essence, about ensuring the exercise of the right to individual self-determination in the relationship between the individual and society, as well as the right to play a social role according to skills and merit. But, it is not only the theory of the social contract that provides for a fair equality of opportunities. Different perspectives of justice contemplate this ideal. As suggested by Tristram Engelhardt Jr individual autonomy must be interpreted as a value in itself and a determining factor for the exercise of a full citizenship. But, justice is an ideal that must be progressively built. Whether in a specific society or on a global scale. And, the great challenge of humanity is precisely to recognize the existing intercultural differences and propose sufficiently flexible ideological systems that can be applied in different countries with very different levels of social and economic development. Without detracting from the ethical principles that should underpin the construction of the 21st century global society.